Safety of Railway Systems and Formal/Semiformal Methods - Milan Slivka (Communications - Scientific letters of the University of Zilina, 2011)
The contribution deals with computer based railway safety systems. It shortly concerns problems associated with using computer systems in comparison with traditional safety systems. The attention is paid to formal and semiformal methods in development and approval of railways systems, seen in the context of standardization and legislation framework. The author summarizes current state of using formal and semiformal methods from whole life cycle point of view of railway safety system in the area of Slovak and Czech railways and possible reasons for their rare use.